Isolation and characterization of anti-proliferative and anti-oxidative mannan from Saccharomyces cerevisiae - Ramy S. Yehia; Ahmed M. Saleh; Mohammad Bani Ismail; Saleh Al-Quraishy; Ohoud Al-Amri; Rewaida Abdel-Gaber (Journal of King Saud University: Science, 2022)
Mannan oligosaccharide is one of the major components of the yeast cell wall. In the present study, the production, characterization, and bioactivity of yeast mannan were investigated. Four indigenous yeast isolates were obtained from various kinds of juice collected from local markets in Al-Ahsa, KSA, and analyzed using morphological and biochemical methods. Isolate RY1 showed the highest production of mannan. RY1 was identified as Saccharomyces cerevisiae based on morphological characteristics and sequencing of the 18S rRNA gene (GenBank accession number LC479088.1). Mannan-RY1 was characterized by polymer analytical methods, 13C and 1H nuclear magnetic resonance spectroscopy (NMR), and infrared spectroscopy (IR). Interestingly, the mannan extracted from RY1 showed a significant ability to scavenge hydroxyl radicals and superoxide anions. In addition, mannan was found to have pronounced anti-tumor activity against liver (HepG2) and breast cancer (MCF7) cell lines. The results presented in this study confirm the bio-therapeutic activity of S. cerevisiae mannan, which could be used as a potential drug for cancer treatment.